A Question of Authority. (2nd January 2021) - Siôn, Tania ap
ABSTRACT: This study offers an example of 'standing theology' as distinguished from sitting theology and kneeling theology. This sermon was given at a service of Holy Eucharist on 27 September 2020 in St Mary's Church, Menai Bridge, Anglesey. This was the third consecutive Sunday of the church being open for services since the first lockdown. The Gospel reading was Matthew 21: 23–32.